Shifts in composition of avian communities related to temperate-grassland afforestation in southeastern South America - Dias,Rafael A. (2013)
Afforestation of temperate grasslands with fast-growing trees for industrial pulpwood production is spreading in South America. Despite high afforestation rates resulting from governmental policies that stimulate pulpwood production in grasslands of southern Brazil and Uruguay, the impact of this activity on biodiversity remains to be properly assessed. We used an Impact-Reference study design to evaluate how grassland afforestation affects the composition of grassland bird assemblages. We sampled eucalyptus plantations and neighboring natural grasslands in southern Brazil from 2006-2009, and relied on nested sampling and analysis to separate the effects of afforestation from the natural variability of grasslands. We recorded a significant difference in composition between assemblages from grasslands and tree plantations. Species adapted to open, treeless areas tended to be negatively affected in relation to edge or forest birds in eucalyptus plantations. Afforestation is systematically replacing the bird assemblage of hilltop grasslands by a collection of common edge and forest species that occur in nearby riverine and hillside forests. Although most grassland birds negatively affected by tree plantations are common and widespread, observed and predicted afforestation rates in southeastern South America may result in regional population reductions in the near future.